2015
DOI: 10.1186/s12898-015-0037-9
|View full text |Cite
|
Sign up to set email alerts
|

Limited impacts of extensive human land use on dominance, specialization, and biotic homogenization in boreal plant communities

Abstract: BackgroundNiche theory predicts that human disturbance should influence the assembly of communities, favouring functionally homogeneous communities dominated by few but widespread generalists. The decline and loss of specialists leaves communities with species that are functionally more similar. Evenness of species occupancy declines, such that species become either widespread of rare. These patterns have often been observed, but it is unclear if they are a general result of human disturbance or specific to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Furthermore, human-modified habitats have been shown to benefit a few widespread species at the expense of many narrowly distributed species (McKinney 2006, Schwartz et al 2006). On the other hand, differences in beta diversity among land uses are not always found, and beta diversity can even increase with human disturbance (Tylianakis et al 2005, Hawkins et al 2015, Mayor et al 2015. The response of beta diversity to land use (both magnitude and direction) varies among taxonomic groups (Fleishman et al 2003, Clough et al 2007, Norfolk et al 2015.…”
mentioning
confidence: 99%
“…Furthermore, human-modified habitats have been shown to benefit a few widespread species at the expense of many narrowly distributed species (McKinney 2006, Schwartz et al 2006). On the other hand, differences in beta diversity among land uses are not always found, and beta diversity can even increase with human disturbance (Tylianakis et al 2005, Hawkins et al 2015, Mayor et al 2015. The response of beta diversity to land use (both magnitude and direction) varies among taxonomic groups (Fleishman et al 2003, Clough et al 2007, Norfolk et al 2015.…”
mentioning
confidence: 99%
“…Most of the studies at a local scale reported that anthropogenic disturbance caused floristic differentiation or absence of the variation of β-diversity [18,19,21], while this study suggested that human disturbance could induce taxonomic homogenization in floodplain landscapes. As revealed by the results of this study, non-native species invasion was responsible for the homogenization in urbanized floodplains.…”
Section: Floristic Homogenization With Degradation Levelsmentioning
confidence: 56%
“…One of the few studies supporting the hypothesis pertaining to disturbed (pioneer) communities was an experiment performed in old fields (Martinez et al, 2015). However, contrary to the mentioned predictions, Mayor et al (2015) found only concave, exponential RSOCs associated with intermediately disturbed boreal forests (but restricted to low-fertility sites), whereas Gibson et al (2005) observed bimodal patterns in OFDs (i.e. sigmoidal RSOCs) through the course of early succession in old fields.…”
Section: Introductionmentioning
confidence: 88%